2005
DOI: 10.1093/jaoac/88.3.761
|View full text |Cite
|
Sign up to set email alerts
|

Multiresidue Method for Determination of Algal Toxins in Shellfish: Single-Laboratory Validation and Interlaboratory Study

Abstract: A method that uses liquid chromatography with tandem mass spectrometry (LC/MS/MS) has been developed for the highly sensitive and specific determination of amnesic shellfish poisoning toxins, diarrhetic shellfish poisoning toxins, and other lipophilic algal toxins and metabolites in shellfish. The method was subjected to a full single-laboratory validation and a limited interlaboratory study. Tissue homogenates are blended with methanol-water (9 + 1), and the centrifuged extract is cleaned up with a hexane was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
83
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(83 citation statements)
references
References 0 publications
0
83
0
Order By: Relevance
“…Liquid chromatography-mass spectrometry (LC-MS) as well as liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS), which together in the following text are termed LC-MS/(MS), methods are increasingly being used in monitoring programs. One method (McNabb et al, 2005), with a LOQ of 40 µg OA/kg shellfish tissue, has undergone an intensive single-laboratory validation and a limited inter-laboratory study, although this study did not include real samples. Some EU Member States are currently using LC-MS/(MS) data to supplement information generated by the MBA by parallel testing.…”
Section: Chemical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid chromatography-mass spectrometry (LC-MS) as well as liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS), which together in the following text are termed LC-MS/(MS), methods are increasingly being used in monitoring programs. One method (McNabb et al, 2005), with a LOQ of 40 µg OA/kg shellfish tissue, has undergone an intensive single-laboratory validation and a limited inter-laboratory study, although this study did not include real samples. Some EU Member States are currently using LC-MS/(MS) data to supplement information generated by the MBA by parallel testing.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…For both matrices, 11 out of 13 laboratories achieved satisfactory z-scores for the total OA-equivalents. Some of the methods in use have been developed to allow multitoxin group detection (Stobo et al 2005, McNabb et al 2005, Fux et al 2007). The available data from in-house and interlaboratory studies suggested that between-laboratory variability was lower when laboratories used their own in-house validated method, than when they adhered to a strictly standardized protocol.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…One multi-toxin LC-MS/MS protocol that included some YTXs (YTX, 45-hydroxyYTX, 1a-homoYTX, carboxyYTX) has been subjected to a limited interlaboratory validation study (McNabb et al, 2005). The limit of quantification (LOQ) for this method was 0.017 mg/kg shellfish.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…The mass spectrometric detection of PTX2 in shellfish extracts has been studied in detail and has been shown to be affected by matrix effects, like many other marine toxins. A collaborative study by McNabb et al (2005) focused on the analysis of extracts and found good apparent recovery. Stobo et al (2005), found little matrix effect in the determination of PTX2 by LC-MS, while Fux et al (2008) found between 0 and 92 % signal enhancement, depending on chromatographic conditions.…”
Section: Chemical Methodsmentioning
confidence: 99%